Frequency of Molar Pregnancies in Health Care Centers of Tehran, Iran - AR Almasi; F Almassinokiani; P Akbari (JRI, 2014)
Background: Hydatidiform mole is an important obstetric problem which can result in harmful and serious outcomes. In this study, an attempt was made to determine the proportion of hydatidiform mole in prenatal clinics of Iran University of Medical Sciences (IUMS) to find the precise frequency of this disease. Methods: Between January 2012 and January 2013, all women who immediately after positive pregnancy test or after retarded menstruation came to prenatal clinics in health care centers of IUMS were included in the study. The women were followed until 8-10 weeks of pregnancy and at this time abdominal sonography was used for confirmation or exclusion of molar pregnancy. Results: In this descriptive study between January 2012 and January 2013, 8614 pregnant women with mentioned criteria were included and 61 cases of hydatidiform mole were diagnosed (0.7% or 7 per 1000 pregnancy). Ten cases (16.4%) were patients with partial moles. There was no significant difference in blood types in molar and non-molar pregnancies, but molar group differed significantly from non-molar group in terms of history of molar pregnancy, abortion, OCP use and ovulation induction. Discussion: Proportion of hydatidiform mole in this study was more than the reported European and American statistics.